The Logic of Quantum Theory Revisited - Suárez, Mauricio (Analysis. Journal of Philosophical Research, 2025)
This article is an unaltered reproduction of my 1992 MSc. dissertation at the London School of Economics and Political Science (LSE), with very minor editorial amendments, and a new introduction explaining why its publication is timely in the wake of the current debate around 'the adoption problem' in the philosophy of logic.